The paradoxical effects of social class on career adaptability: The role of intolerance of uncertainty - Wang, Ruimeng; Lin, Xinqi; Wang, Le (Frontiers in Psychology, 2022)
As a growth background factor, family social class has far-reaching effects on youth career development. However, we have limited understanding of the role and functional mechanisms of social class in career adaptability. Based on the social cognitive theory of social class, we examine the mediating role of intolerance of uncertainty in the relationship between youths’ subjective social class and career adaptability. We also explore the moderating influences of self-esteem. Data were collected from a sample consisting of 712 undergraduates (63.2% female) in China. Results show that subjective social class positively impacts career adaptability via prospective anxiety, and negatively impacts career adaptability via inhibitory anxiety. The intensity of these indirect relationships is contingent on youths’ self-esteem. Our study illustrates the complex and paradoxical effects of social class on career adaptability and has important theoretical and practical implications. This study expands the theoretical perspective by bringing in the social cognitive theory of social class, provides novel insight into the complex interaction between individuals and the environment in youth career development, and should provide inspiration for the design of career intervention programs.